Extracellular vesicles and chronic inflammation during HIV infection. Issue 1 (6th November 2019) - Pérez, Paula Soledad; Romaniuk, María Albertina; Duette, Gabriel A.; Zhao, Zezhou; Huang, Yiyao; Martin‐Jaular, Lorena; Witwer, Kenneth W; Théry, Clotilde; Ostrowski, Matías
ABSTRACT: Inflammation is a hallmark of HIV infection. Among the multiple stimuli that can induce inflammation in untreated infection, ongoing viral replication is a primary driver. After initiation of effective combined antiretroviral therapy (cART), HIV replication is drastically reduced or halted. However, even virologically controlled patients may continue to have abnormal levels of inflammation. A number of factors have been proposed to cause inflammation in HIV infection: among others, residual (low‐level) HIV replication, production of HIV protein or RNA in the absence of replication, microbial translocation from the gut to the circulation, co‐infections, and loss of immunoregulatory responses. Importantly, chronic inflammation in HIV‐infected individuals increases the risk for a number of non‐infectious co‐morbidities, including cancer and cardiovascular disease. Thus, achieving a better understanding of the underlying mechanisms of HIV‐associated inflammation in the presence of cART is of utmost importance. Extracellular vesicles have emerged as novel actors in intercellular communication, involved in a myriad of physiological and pathological processes, including inflammation. In this review, we will discuss the role of extracellular vesicles in the pathogenesis of HIV infection, with particular emphasis on their role as inducers of chronic inflammation.